2017
DOI: 10.1016/j.jnutbio.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Raspberry pomace alters cecal microbial activity and reduces secondary bile acids in rats fed a high-fat diet

Abstract: ReuseUnless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or other rights-holder may allow further reproduction and re-use of this version -refer to the White Rose Research Online record for this item. Where records identify the publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 58 publications
2
22
0
1
Order By: Relevance
“…The health benefits associated with these substances are various and relate in part to the inhibition of digestive enzymes [13], a decrease of oxidative stress [14], and a change in the gut microbiota [15]. Ellagitannins from red raspberry exert cytotoxic effects against human colon adenocarcinoma in vitro [16] and reduce secondary bile acids in rats fed a high-fat diet [17]. Other fruits such as pomegranate also contain ellagitannins, and this fruit has been shown to have anti-inflammatory and antitumoral properties [18], to promote a protective effect in obesityassociated nonalcoholic fatty liver disease [19], to help ameliorate metabolic syndrome [20], and to reduce thiobarbituric acid reactive substances in overweight subjects [21].…”
Section: Introductionmentioning
confidence: 99%
“…The health benefits associated with these substances are various and relate in part to the inhibition of digestive enzymes [13], a decrease of oxidative stress [14], and a change in the gut microbiota [15]. Ellagitannins from red raspberry exert cytotoxic effects against human colon adenocarcinoma in vitro [16] and reduce secondary bile acids in rats fed a high-fat diet [17]. Other fruits such as pomegranate also contain ellagitannins, and this fruit has been shown to have anti-inflammatory and antitumoral properties [18], to promote a protective effect in obesityassociated nonalcoholic fatty liver disease [19], to help ameliorate metabolic syndrome [20], and to reduce thiobarbituric acid reactive substances in overweight subjects [21].…”
Section: Introductionmentioning
confidence: 99%
“…To induce obesity-related changes in the hepatocytes (HepG2 cells), plasma samples obtained from a preclinical study using Wistar rats fed with a high-fat diet were used [ 18 ]. The plasma samples from an in vivo model of a high-fat diet contained significantly higher values of the total cholesterol (TC) and triglycerides (TG) in comparison to the animals fed with a standard diet for laboratory rodents ( p ≤ 0.05; Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a nutritional study performed on rats with metabolic syndrome symptoms induced by a high-fat diet showed that ellagic acid attenuates diet-induced impairment of glucose tolerance and reduces NF-κB protein levels in the liver [ 17 ]. In addition, our previous nutritional experiments with dietary extracts from raspberries have indicated that these extracts are effective at decreasing total triglycerides and cholesterol in the blood and modulate hepatic lipid metabolism in rats fed with a high-fat diet [ 18 , 19 , 20 ]. The regulatory effects observed in the liver partially support the hypothesis that raspberry extracts can reduce liver disorders induced by a high-fat diet.…”
Section: Introductionmentioning
confidence: 99%
“…The HF diet also increased hepatic cholesterol and triglyceride levels by approximately four and two times, respectively (compared with the C group). Studies on HF diets, including those conducted in our laboratory, have suggested that such a considerable hepatic cholesterol accumulation cannot be achieved in rats by only a high dietary fat content [ 24 , 25 ]. For example, the study by Quesada et al [ 24 ] showed that the cholesterol accumulation in rats fed an HF diet for 12 weeks, although significantly higher, is not even 2 times greater.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, cholic acid is one of two primary bile acids synthesized by the human liver, which facilitates digestion and absorption of dietary lipids [ 26 ]. However, this compound is minor in rats, in which muricholic acids are the main bile acids synthesized by the liver [ 25 ]. Interestingly, the HF diet containing cholic acid used in the present study had minor, but still negative influence on the blood lipid profile, decreasing only the HDL cholesterol concentration.…”
Section: Discussionmentioning
confidence: 99%